Fabrication of high-performance thin-film composite and nanochannel-enabled next-generation membranes for water desalination - Lim, Yu Jie (Nanyang Technological University, 2023)
Water reuse and seawater desalination have evolved into alternative water sources in the last 40 years in response to the increasing freshwater scarcity. Seawater reverse osmosis (SWRO) is the key technology driving an energy-efficient and cost-effective desalination process. At the heart of SWRO is the membrane unit, which comprises semi-permeable membranes capable of separating salts from water. Because of the high pressure needed to pressurize the feed water against the membrane, the power consumption by the high-pressure pumps is the highest in an SWRO process. It is therefore imperative to develop robust and high performance membranes to minimize the energy consumption of desalination. The main objective of this study is to explore the niche fabrication methods of high-performance RO membranes from a bottom-up approach involving polymers and nanochannels. First, a module-scale simulation was conducted to examine the impact and actual significance of the benefits which highly permeable membranes could bring about at a system-level (Chapter 3). Based on this theoretical understanding, Chapter 4 studies the possibility to fabricate robust and high-performance membranes by optimizing the support layer of thin-film composite (TFC)-SWRO membranes. Because the performance of a composite membrane is determined by both the support and active layer, it was attempted to scrutinize the nanoscale characteristics of the polyamide active layer that determine the separation capabilities of TFC membranes (Chapter 5). However, empirical evidence has shown that it is difficult to obtain revolutionary performances by optimizing the dense selective layer of RO membranes due to the permeability-selectivity tradeoff. Therefore, Chapters 6 and 7 seek to study the possibility to overcome this tradeoff by incorporating novel nanomaterials into the dense selective layer to provide supplementary water transport pathways. In the first approach, pillar[5]arene channels were incorporated in the form of channel-containing liposomes (size of ~120 nm). In the second approach, the practicability of synthesizing biomimetic membranes via a more facile approach was explored by immobilizing water channels into the selective layer as nanoparticles. In summary, this thesis provides new insights into the fabrication of composite membranes for water desalination applications, as well as how nanochannels can be leveraged on to fabricate next-generation membranes that may be capable of overcoming the permeability-selectivity tradeoff.